Scientists develop new digital tools for enhancing water management in a changing climate - Reddy, Nagarjuna N.; Garg, Kaushal K.; Singh, Ramesh (International Crops Research Institute for the Semi-Arid Tropics, 2025)
Agricultural decision-making often faces challenges due to fragmented data and limited access to field-specific information. Farmers and resource managers frequently make critical choices without a holistic understanding of landscape characteristics and resource availability. To overcome this limitation, a digital decision dashboard is being developed to integrate landscape-level datasets with plot-scale decision support. This platform brings together multiple layers of information such as soil properties, land use, land slope, and infrastructure on a single interface to enable informed, site-specific, and resource-efficient decisions.